Variaçáo da porosidade da cortiça determinismo fenotípico - Fonseca, Fortunato M. A.; Louzada, José Luis P. C.; Gomes, César A. M. (II Congreso Forestal Español, 1997)
Analyses were made of the variation in the porosity of cork collected from 100 trees at the BHD level and in 30 trees, with reproduction cork collected at three levels of height with a fourth level of virgin cork. Despite verifying the recognizable and elevated variability (1 to 10) among trees, it (44%) is greatly exceeded by the internal variability (56%) of the porosity of cork in the individuals, without a presumable systematization with the growth or funcionality. The phenotype determinism, within the reproduction corks for the number of pores is relatively elevated (R2 =40% to 60%) but already reduced (R2 =20% to 30%) for the porosity. On the other hand, there doesn't exist any such type of phenotypical determinism between the poro sities of reproduction cork anf of virgin cork, something which also supports the hypothesis of elevated abnormalities or reaction in the formation of reproduction cork.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español issue: 1982 pub-location: Pamplona
Keywords: Cork; phenotypical determinismo; Porosity; variation